Relation between vitamin D status and body composition in collegiate athletes - Hollis, B. W.; Larson-Meyer, D. E.; Heller, J. E.; Thomas, J. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Excess body fat or obesity is known to increase risk of poor vitamin D status in nonathletes but it is not known if this is the case in athletes. Furthermore, the reason for this association is not understood, but is thought to be due to either sequestration of the fat-soluble vitamin within adipose tissue or the effect of volume dilution related to obese individuals` larger body size. Forty two US college athletes (24 men 18 women, 20.7 ± 1.6 years, 85.0 ± 28.7 kg, BMI = 25.7 ± 6.1 kg/m2) provided blood samples during the fall and underwent measurement of body composition via dual energy X-ray absorptiometry. Serum samples were evaluated for 25-hydroxyvitamin D (25(OH)D) concentration to assess vitamin D status using Diasorin 25(OH)D radioiodine assay. Serum 25(OH)D concentration was negatively associated with height (r = -0.45), total body mass (r = -0.57), BMI (r = -0.57), body fat percentage (r = -0.45), fat mass (r = -0.60) and fat-free mass (r = -0.51) (p < .05). These associations did not change after controlling for sex. In a linear regression mixed model, fat mass (coefficient -0.47, p = .01), but not fat-free mass (coefficient -0.18, p = .32) significantly predicted vitamin D status and explained approximately 36% of the variation in serum 25(OH)D concentration. These results suggest that athletes with a large body size and/or excess adiposity may be at higher risk for vitamin D insufficiency and deficiency. In addition, the significant association between serum 25(OH)D concentration and fat mass in the mixed model, which remained after controlling for sex, is in support of vitamin D sequestration rather than volume dilution as an explanation for such association.